THE ROLE OF PSYCHOLOGICAL DIAGNOSIS IN CLINICAL PRACTICE (Conferencea, 2022)
The article discusses the importance, goals and objectives of medical psychological diagnostics in the field of psychiatry, as well as the study of emotional disorders, in particular schizophrenia, its impact on the motivational sphere of the individual.